Alternative splicing of the TNFSF13B (BAFF) pre-mRNA and expression of the BAFFX1 isoform in human immune cells - Stelmach, Patrick; Pütz, Michael; Pollmann, Robert; Happel, Michael; Stei, Susanne; Schlegel, Kerstin; Seipelt, Maria; Eienbröker, Christian; Eming, Rüdiger; Mandic, Robert; Huber, Magdalena; Tackenberg, Björn (Gene, 2020)
Human B cell activating factor (TNFSF13B, BAFF) is a tumor necrosis factor superfamily member. Binding its unique receptor (TNFRSF13C, BAFF-R) mediates gene expression and cell survival in B cells via activation of NFκB pathway. Furthermore, there is data indicating a role in T cell function. A functionally inhibitory isoform (ΔBAFF) resulting from the deletion of exon 3 in the TNFSF13B pre-RNA has already been reported. However, data on the complexity of post-transcriptional regulation is scarce. Here, we report molecular cloning of nine TNFSF13B transcript variants resulting from alternative splicing of the TNFSF13B pre-mRNA including BAFFX1. This variant is characterized by a partial retention of intron 3 of the TNFSF13B gene causing the appearance of a premature stop codon. We demonstrate the expression of the corresponding BAFFX1 protein in Jurkat T cells, in ex vivo human immune cells and in human tonsillar tissue. Thereby we contribute to the understanding of TNFSF13B gene regulation and reveal that BAFF is regulated through a post-transcriptional mechanism to a greater extent than reported to date.
Gesehen am 17.11.2020